Activation of nuclear factor‐κB in the angiogenesis of glioma: Insights into the associated molecular mechanisms and targeted therapies. (10th December 2020) - Tu, Jiajie; Fang, Yilong; Han, Dafei; Tan, Xuewen; Jiang, Haifeng; Gong, Xun; Wang, Xinming; Hong, Wenming; Wei, Wei
Abstract: Glioma is the most commonly observed primary intracranial tumour and is associated with massive angiogenesis. Glioma neovascularization provides nutrients for the growth and metabolism of tumour tissues, promotes tumour cell division and proliferation, and provides conditions ideal for the infiltration and migration of tumour cells to distant places. Growing evidence suggests that there is a correlation between the activation of nuclear factor (NF)‐κB and the angiogenesis of glioma. In this review article, we highlighted the functions of NF‐κB in the angiogenesis of glioma, showing that NF‐κB activation plays a pivotal role in the growth and progression of glioma angiogenesis and is a rational therapeutic target for antiangiogenic strategies aimed at glioma. Abstract : Growing evidence suggests that there is a correlation between the activation of nuclear factor (NF)‐κB and the angiogenesis of glioma. Herein, we sought to discuss the current understanding of the molecular mechanisms of NF‐κB in diverse glioma microenvironments such as hypoxia, inflammation, and oxidative stress, and its function as a therapeutic target for antiangiogenic strategies aimed at glioma.